A Review of Social Media Restrictions for Children in Indonesia - Grace Juanita; Tristam Pascal Moeliono; Lidwina Larasati Himawan; Vionna Angeline Chandra (Lembaga Bale Literasi, 2026)
The growing use of social media platforms by adolescents presents serious challenges such as cyberbullying, data exploitation and adverse psychological effects. Hence, strong regulatory frameworks are essential. This research aims to analyze the legal framework on the limitation of social media for minors in Indonesia and to compare it with the practices in the United States of America and Australia. The research is developed from the standpoint of legislation and comparative law, the normative juridical technique. The main legal tools are Government Regulation No. 17 of 2025 (Indonesia), Arkansas Act 689 (United States), the Online Safety Amendment Act 2024 (Australia) and relevant international human rights treaties. Secondary sources are scholarly publications , journal articles , government papers etc . The data were acquired by document review and evaluated using qualitative technique with descriptive analysis. Data veracity was assured by source triangulation and rigorous legal interpretation. “It exposes a huge split in how regulators. The United States ruled that Arkansas Act 689 was unconstitutional because it violated the strong First Amendment right to free expression. Australia has taken a tough prohibitionist stance with large financial penalties for platforms that do not comply. Mental health and safety of children are the top priority Government Regulation No. 17 of 2025 of the Indonesian Government has implemented the age categorisation and risk-based access plan that requires parental authorisation and imposes considerable cost on electronic system providers. Like any administrative statute, it has its own challenges, including low levels of digital literacy, uneven technology infrastructure across the archipelago, pushback from global platforms and the absence of an independent supervision body and comprehensive means for victim compensation. The research says more collaboration across sectors, a stronger regulatory framework and higher levels of digital literacy are needed to create a truly safe digital ecosystem for children.